Other- and Self-Directed Forms of Violence and Their Relationships to DSM-IV Substance Use and Other Psychiatric Disorders in a National Survey of Adults - Harford, Thomas C. (2013)
OBJECTIVE: To examine associations between DSM-IV psychiatric disorders and other- and self- directed violence in the general population. METHODS: Data were obtained from the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) Waves 1 & 2 (n=34,653). Four violence categories were derived from a latent class analysis (LCA) of 5 other-directed and 4 self-directed violent behavior indicators. Multinomial logistic regression examined class associations for gender, race-ethnicity, age and DSM-IV substance use, mood, anxiety, and personality disorders. RESULTS: Approximately 16% of adults reported some form of violent behavior distributed as follows: other-directed only, 4.6%; self-directed only, 9.3%; combined self- and other-directed, 2.0%; and no violence, 84.1%. The majority of the DSM-IV disorders included in this study were significantly and independently related to each form of violence. Generally, other-directed violence was more strongly associated with any substance use disorders (81%) and any personality disorders (42%), while self-directed violence was more strongly associated with mood (41%) and anxiety disorders (57%). Compared with these two forms of violence, the smaller group with combined self- and other-directed violence was more strongly associated with any substance use disorders (88%), mood disorders (63%), and personality disorders (76%). CONCLUSION: Findings from this study are consistent with recent conceptualizations of disorders as reflecting externalizing disorders and internalizing disorders. The identification of the small category with combined forms of violence further extends numerous clinical studies which established associations between self- and other-directed violent behaviors. The extent to which the combined violence category represents a meaningful and reliable category of violence requires further detailed studies.